Intermediate Access 2007 - Miles, Timothy; Safari eBooks ([S.l.] : CompuWorks, 2013)
"This course builds on the skills and concepts taught in Access 2007: Introduction. Students will learn how to normalize data; work with Lookup fields and subdatasheets; create join queries; add objects to forms, print reports and labels; create charts; and use PivotTables and PivotCharts. Designated as Approved Courseware for the Microsoft Certified Application Specialist program, this course will help students prepare for the Access 2007 exam (77-605). For comprehensive certification training, students should complete Access 2007: Introduction, Intermediate, and Advanced."--Resource description page.
Title from title screen.
Publication information taken from resource description page (viewed August 26, 2013).
Presenter, Timothy Miles.
Keywords: Microsoft Access; Database management; Business -- Computer programs; Electronic books